Compact Spinning in Cotton-based Core-spun Yarn: A Review - Rashid, Ehsanur; Ul Haque, Raihan; Khan, Rubel (European Scientific Journal, ESJ, 2021)
In today’s world, textile outfits are chosen not only for their functional properties but also for their comfort. As cotton is synonymous with comfort in textile industries, cotton-based core-spun yarn is becoming increasingly popular day by day, where the core element satisfies the functional properties and the cotton sheath provides a good hand feel and comfort. At the beginning of the twenty-first century, researchers developed a new spinning modification known as the compact spinning system to improve yarn quality. In cotton-based compact core-spun yarn, reduced hairiness, unevenness (U%), thick place, thin place, neps, and increased strength are achieved. This will also lead to significant abrasion and piling resistance, higher air permeability, lower thermal resistance, and higher Relative Water Vapor Permeability (RWVP). This review paper illustrates the advantages of spinning cotton-based core-spun yarn in the compact spinning system.